A Requirement of Protein Geranylgeranylation for Chemokine Receptor Signaling and Th17 Cell Function in an Animal Model of Multiple Sclerosis - Swan, Gregory; Geng, Jia; Park, Eunchong; Ding, Quanquan; Zhou, John; Walcott, Ciana; Zhang, Junyi J.; Huang, Hsin-I; Hammer, Gianna Elena; Wang, Donghai (Frontiers in Immunology, 2021)
Precisely controlled lymphocyte migration is critically required for immune surveillance and successful immune responses. Lymphocyte migration is strictly regulated by chemokines and chemokine receptors. Here we show that protein geranylgeranylation, a form of post-translational protein lipid modification, is required for chemokine receptor-proximal signaling. Mature thymocytes deficient for protein geranylgeranylation are impaired for thymus egress. Circulating mature T cells lacking protein geranylgeranylation fail to home to secondary lymphoid organs or to transmigrate in response to chemokines in vitro. Mechanistically, protein geranylgeranylation modifies the 𝛾-subunit of the heterotrimeric small GTPases that are essential for chemokine receptor signaling. In addition, protein geranylgeranylation also promotes the differentiation of IL-17-producing T helper cells while inhibiting the differentiation of Foxp3+ regulatory T cells. Finally, mice with T cell lineage-specific deficiency of protein geranylgeranylation are resistant to experimental autoimmune encephalomyelitis induction. This study elucidated a critical role of protein geranylgeranylation in regulating T lymphocyte migration and function.